Etnobotânica e estrutura populacional da mangabeira (Hancornia speciosa Gomes) em assentamento agroextrativista, Pirambu, Sergipe, Brasil - Lima, Thaiane Natalle Moreira (2019)
The only Agrarian Reform Settlement Project with the Agroextractive modality is located in the municipality of Pirambu, Sergipe State. Known as PAE São Sebastião, it was created with the focus on income generation from the extraction and sale of the fruits of mangabeira tree (Hancornia speciosa Gomes; Apocynaceae). The present study investigated the residents of the PAE São Sebastião in relation to their knowledge about and management forms of the species. The population structure of H. speciosa in the productive lots was also analyzed. Semi-structured interviews and tools of the Participatory Rapid Diagnosis (DRP) were performed with 31 residents of the settlement. Both the development stage and the diameter class, by means of a qualitative and quantitative census, were used in order to evaluate the population structure. The results indicate that the collectors have some knowledge about the species; however it is necessary to develop standardized methods of collection and management. The way it is currently done results in the breaking of branches and the felling of flowers. A total of 1.154 mangabeira trees were recorded, resulting in a density of 14.5 individuals per hectare. Apparently, the population of H. speciosa in the PAE São Sebastião is not growing, since it presents a predominance of individuals distributed in the intermediate diameter classes, which may compromise the continuation of fruit extractive activity in the area.